2005
DOI: 10.1097/01.sla.0000154149.85506.36
|View full text |Cite
|
Sign up to set email alerts
|

Functional Recovery After Open Versus Laparoscopic Colonic Resection

Abstract: Functional recovery after colonic resection is rapid with a multimodal rehabilitation regimen and without differences between open and laparoscopic operation. Further large-scale studies are required on potential differences in serious morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
334
7
27

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 412 publications
(380 citation statements)
references
References 30 publications
12
334
7
27
Order By: Relevance
“…Other findings suggest that patients who undergo an open procedure have a shorter LOS and that laparoscopic patients have a higher pain score. 75 Despite the studies reported herein and the position expressed in this document by some members of the Panel, the issue as to whether or not the duration of POI is shortened by laparoscopic procedures compared with open procedures is still under active study. Definitive conclusions about this controversy must await the results of large randomized trials.…”
Section: Laparoscopic Surgery Vs Open Surgical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Other findings suggest that patients who undergo an open procedure have a shorter LOS and that laparoscopic patients have a higher pain score. 75 Despite the studies reported herein and the position expressed in this document by some members of the Panel, the issue as to whether or not the duration of POI is shortened by laparoscopic procedures compared with open procedures is still under active study. Definitive conclusions about this controversy must await the results of large randomized trials.…”
Section: Laparoscopic Surgery Vs Open Surgical Proceduresmentioning
confidence: 99%
“…To elucidate these issues, Basse and colleagues 75 conducted a randomized observer-and-patient blinded trial of 60 patients (median age, 75 years) who underwent elective laparoscopic or open colonic resection with fast-track rehabilitation and planned discharge after 48 hours. Functional recovery was assessed in detail during the first postoperative month.…”
Section: Laparoscopic Surgery Vs Open Surgical Proceduresmentioning
confidence: 99%
“…Minimally, invasive surgery has minimized the somatic wound and should have neutralized the impediment to convalescence absolutely. But, the evidence has been to contrary, in a setting of level 1 designed study for colorectal operations [11]. It is therefore the importance of autonomic wound of abdominal surgery that needs to be considered.…”
mentioning
confidence: 99%
“…Or consider the study comparing open colectomy to laparoscopic colectomy performed by Basse et al [16]. They randomly assigned 60 patients to one of these modes of surgery and, at the conclusion of the case, went to the considerable effort of covering the entire abdomen with a single large bandage.…”
mentioning
confidence: 99%